2020
DOI: 10.1101/2020.06.10.138578
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Inhibition underlies fast undulatory locomotion inC. elegans

Abstract: 239, Introduction 651, Discussion 1500• Conflict of interest statementThe authors declare no conflicts of interest.• Acknowledgments LD thanks her thesis committee: Farzan Nadim, Daphne Soares, Andrew Leifer, and Eric Fortune for useful discussions, encouragement, and support. JED and NC thank Thomas Ranner for useful and critical discussions. Some strains were provided by the CGC, which is funded by the NIH Office of Research Infrastructure Programs (P40 OD010440).We also thank the National Bioresource Projec… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 77 publications
0
5
0
Order By: Relevance
“…Given the deliberate effort to remove from the model a number of components that are known to play important roles in forward locomotion for the sake of addressing a question that had not been tackled yet, the model naturally reveals discrepancies with a number of experiments. Specifically, there is evidence that: silencing A-class motor neurons does not entirely disrupt forward locomotion [87]; ablating AS does not disrupt forward locomotion entirely but leads to a ventral bias in the bending [77]; and D-class motor neurons may not be playing a role in coordinating body waves under certain conditions [20, 58]. In contrast, the multiple network rhythmic pattern generators hypothesis in this model relies on the participation of all motor neurons, including classes A, AS, and D. Although there is further experimental work that remains to delineate with precision the role of each of those neurons in forward locomotion, there is one relatively trivial way to resolve the inconsistency between the model and the hypothesis that those neurons play no substantial roles in forward locomotion: the re-introduction of proprioceptive feedback back into the model as an independent mechanism for generating reflexive rhythmic patterns.…”
Section: Discussionmentioning
confidence: 99%
“…Given the deliberate effort to remove from the model a number of components that are known to play important roles in forward locomotion for the sake of addressing a question that had not been tackled yet, the model naturally reveals discrepancies with a number of experiments. Specifically, there is evidence that: silencing A-class motor neurons does not entirely disrupt forward locomotion [87]; ablating AS does not disrupt forward locomotion entirely but leads to a ventral bias in the bending [77]; and D-class motor neurons may not be playing a role in coordinating body waves under certain conditions [20, 58]. In contrast, the multiple network rhythmic pattern generators hypothesis in this model relies on the participation of all motor neurons, including classes A, AS, and D. Although there is further experimental work that remains to delineate with precision the role of each of those neurons in forward locomotion, there is one relatively trivial way to resolve the inconsistency between the model and the hypothesis that those neurons play no substantial roles in forward locomotion: the re-introduction of proprioceptive feedback back into the model as an independent mechanism for generating reflexive rhythmic patterns.…”
Section: Discussionmentioning
confidence: 99%
“…Laser ablation studies have shown that the cholinergic B-type motor neurons are required for forward locomotion (Chalfie et al, 1985). The GABAergic D-type motor neurons provide dorsoventral cross-inhibition to the body wall muscles and are essential for maintaining normal wave shape and frequency during forward locomotion (Deng et al, 2020; Mclntire et al, 1993). A set of premotor interneurons (AVB, PVC, AVA, AVD, and AVE) regulate forward and reverse movements (Chalfie et al, 1988; Driscoll and Kaplan, 1997; Von Stetina et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…However, recent advances streamlined and made affordable the automated study and quantification of behavior in C. elegans and other organisms. For example, the Haspel lab at NJIT made use of the recently developed TIERPSY behavioral software (Avelino et al 2018) to build numerous worm tracking systems that are at once user friendly, and able to achieve levels of kinematic analysis that previously required considerably more expensive setups (Deng et al 2020).…”
Section: Descriptionmentioning
confidence: 99%
“…Many systems have been developed over the years and are currently used across the world for the rapid and unbiased quantification of behavioral phenotypes. For example, we have used tracking systems in the past to compare the ability of mutant strains to transition between gaits (Vidal-Gadea et al, 2011), and Deng and colleagues to study the role of inhibition during locomotion (Deng et al, 2020, see Husson et al 2012 for a review of the use of tracking systems in C. elegans). Until recently, the automated quantification of C. elegans behavior was only feasible for a few wealthy (or specialized) labs.…”
Section: Descriptionmentioning
confidence: 99%